2013
DOI: 10.1080/00480169.2013.852447
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary provision of analgesia for domestic cats (Felis catus) undergoing gonadectomy: a comparison of samples from New Zealand, Australia and the United Kingdom

Abstract: Contemporary use of analgesics for cats appears focused on provision at clinic and may not address the effects of surgery beyond the first 24 hours. The UK, Australia and New Zealand clearly differ in the types of analgesia administered, possibly reflecting differing professional considerations of the risks associated with the use of NSAID. In the interests of animal welfare, pain relief should perhaps be provided or offered more frequently for owner administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 28 publications
(36 reference statements)
3
29
1
Order By: Relevance
“…The present survey requested data relating to total perioperative use of analgesics, rather than an assessment of preincisional versus postincisional data, but our results were very similar to the findings of Farnworth and others (2014).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The present survey requested data relating to total perioperative use of analgesics, rather than an assessment of preincisional versus postincisional data, but our results were very similar to the findings of Farnworth and others (2014).…”
Section: Discussionsupporting
confidence: 73%
“…This figure was lower in cats, with only a quarter of respondents prescribing NSAIDs for longer than 24 hours after castration. The recent survey by Farnworth and others (2014) indicated a much lower prevalence of prescription of postdischarge analgesics for feline neutering than was indicated by the responses to the present survey. However, a number of respondents to the current survey indicated that they considered a single subcutaneous dose of carprofen to provide up to 72 hours analgesia in cats, and these respondents may have also indicated that they provided NSAID analgesia for greater than 24 hours postoperatively, potentially artificially increasing the number of prescribers of postoperative NSAIDs in cats.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Due to the difficulty of identifying pain in animals, the postoperative treatment can often be inappropriate [10][11] . Thus, the development of more accurate methods of evaluation is crucial for optimal management of pain.…”
Section: Introductionmentioning
confidence: 99%